Association between the immune-inflammation indicators and osteoarthritis - NHANES 1999–2018 - Yan Xue; Cheng Chang; Yajun Chen; Lang Jia; Han Wang; Zaoyang Liu; Jiang Xie (Osteoarthritis and Cartilage Open)
Background: Investigate the link between systemic immune-inflammatory index (SII) and Systemic Immune Response Index (SIRI) with osteoarthritis (OA) using National Health and Nutrition Examination Survey (NHANES) data (1999–2018). Methods: Extracted NHANES data (1999–2018) and selected a study population based on demographic, examination, and laboratory data. Calculated SII (platelet count ​× ​neutrophil count/lymphocyte count) and SIRI (neutrophil count ​× ​monocyte count/lymphocyte count). Employed multivariate logistic regression and restricted cubic spline (RCS) regression for Ln-SII, SIRI, and OA relationship investigation. Conducted subgroup analyses. Results: Study involved 32,144 participants (16,515 males, 15,629 females), with 12.16% having OA. Positive correlation between highest SII quartile and OA in unadjusted and adjusted model 1 (Unadjusted Model, P ​< ​0.001; Model 1, P ​= ​0.01). In Model 2, adjusting for all factors, positive correlation observed, not statistically significant (Model 2, P ​= ​0.07). Similar SIRI-OA correlation trends from Unadjusted Model to Model 2 (Unadjusted Model, P ​< ​0.0001; Model 1, P ​< ​0.0001; Model 2, P ​< ​0.001). Subgroup analysis found no significant factors. Identified critical point at ln-SII ≈6.39 (SII ​= ​595.86), beyond which OA prevalence significantly increased. No potential nonlinear SIRI-OA association (NL-P value ​> ​0.05). Conclusion: When SII exceeds 595.86, OA prevalence may rise. Besides, there was a significant positive correlation between SIRI and OA prevalence. SII and SIRI may be useful markers for OA research, warranting further exploration in this area.